Onboarding dataverse repositories in OpenAIRE Provide: a gateway to the EOSC - Príncipe, Pedro (2023)
This proposal aims to present the OpenAIRE PROVIDE Dashboard service, detailing the main features and functionalities available for all the managers of data sources that are part or want to integrate the OpenAIRE infrastructure and are aiming to onboard research products in the EOSC catalogue. The OpenAIRE PROVIDE Dashboard is a bundle of services for content providers to share and exchange metadata and content using the European Open Science Cloud (EOSC) metadata frameworks and rules of participation. Is a one-stop-service with added value services where content providers interact with OpenAIRE by validating and enriching the data source metadata and content and providing detailed information about the metadata aggregation stages and consolidated usage statistics reports.